Assessing for cryptorchidism via telehealth is not always accurate: A Paediatric cohort study - McBride, Craig A.; Patel, Bhaveshkumar; Xu, Eileen; Bairagi, Anjana (Frontiers in Urology, 2022)
Background Cryptorchidism is the most common referral to our paediatric surgical telehealth service. There is a paucity of literature on this condition in a telehealth context. We wished to determine the accuracy of telehealth in the diagnosis of cryptorchidism, and to examine for any predictors that may increase diagnostic confidence. Methods Retrospective analysis of a consecutive cohort from November 2009 (start of service) to December 31st 2021. Data from telehealth were compared against eventual surgical outcomes. Results There were 387 consecutive patients seen, resulting in 335 bookings for orchidopexy. 69/327 patients presenting for operation did not have an orchidopexy performed. Operations did not proceed as booked for 37% of children. Referrals for bilateral cryptorchidism were more likely to be normal on face to face review. The average round-trip distance for families from home to hospital, and back, was 948km. Conclusions Telehealth is not an accurate method for assessing cryptorchidism. Operations were cancelled for 1 in 5 children, and altered for 3 in 8. Travel distances for families were significant. The inaccuracy of telehealth for assessing cryptorchidism must balance inconvenience for families against disruption to elective operating lists.